Commercial Banks As Facilitators Of Electronic Payment System For E-Commerce In Malaysia - Veerasamy, Sigamani M (2001)
This research focuses on the factors that influence the adoption of Electronic Commerce Payment System (ECP) in the e-commerce transactions by merchants in Malaysia. The aim of this study is to evaluate the merchants' perceptions of the ECPS and the role commercial banks play in facilitating this service. Through the results obtained, recommendations are made to the bankers on various issues including the targer sector of merchants for this type of business.